Relocalizing Genetic Loci into Specific Subnuclear Neighborhoods - Lee, Hsiang-Ying (American Society for Biochemistry and Molecular Biology, 2011)
A poorly understood problem in genetics is how the three-dimensional organization of the nucleus contributes to establishment and maintenance of transcriptional networks. Genetic loci can reside in chromosome “territories” and undergo dynamic changes in subnuclear positioning. Such changes appear to be important for regulating transcription, although many questions remain regarding how loci reversibly transit in and out of their territories and the functional significance of subnuclear transitions. We addressed this issue using GATA-1, a master regulator of hematopoiesis implicated in human leukemogenesis, which often functions with the coregulator Friend of GATA-1 (FOG-1). In a genetic complementation assay in GATA-1-null cells, GATA-1 expels FOG-1-dependent target genes from the nuclear periphery during erythroid maturation, but the underlying mechanisms are unknown. We demonstrate that GATA-1 induces extrusion of the β-globin locus away from its chromosome territory at the nuclear periphery, and extrusion precedes the maturation-associated transcriptional surge and morphological transition. FOG-1 and its interactor Mi-2β, a chromatin remodeling factor commonly linked to repression, were required for locus extrusion. Erythroid Krüppel-like factor, a pivotal regulator of erythropoiesis that often co-occupies chromatin with GATA-1, also promoted locus extrusion. Disruption of transcriptional maintenance did not restore the locus subnuclear position that preceded activation. These results lead to a model for how a master developmental regulator relocalizes a locus into a new subnuclear neighborhood that is permissive for high level transcription as an early step in establishing a cell type-specific genetic network. Alterations in the regulatory milieu can abrogate maintenance without reversion of locus residency back to its original neighborhood.